Perusmerkkilaulut - Tamminen, Jussi; Holma, Juha, 1960-; Kiiski, Paavo, 1942-2022; Lindqvist, Antti; Salakka, Teppo, 1959-; Tamminen, Jussi, (kuoronjohtaja) ([Helsinki] : Mieskuoroliitto, 2004)
40 kappaletta.
Lisäpainokset: 2. p. 2004. - 3. p. 2005. - 4. p. 2005. - 5. p. 2006. - 5. p. 2006.
Soitinnus: mieskuoro.
Sanat: suomi, osittain muita kieliä.
[Nuottijulkaisu]
Keywords: kuoromusiikki; körmusik